Professor at large : the Cornell years - Cleese, John (Cornell University Press, 2018)
"Comedian and actor John Cleese in the role of Ivy League professor at Cornell University, where he is currently professor-at-large. This book includes a selection of talks, essays, and lectures and provides a unique view of Cleese's endless pursuit of intellectual discovery across a range of topics"--